Antimycobacterial activity of a new peptide Polydim-I isolated from neotropical social wasp Polybia dimorpha - Neves, Rogério Coutinho das (2016)
Mycobacterium abscessus subsp. massiliense, a rapidly growing mycobacteria (RGM) that is becoming increasingly important among human infectious diseases, is virulent and pathogenic and presents intrinsic resistance to several antimicrobial drugs that might hamper their elimination. Therefore, the identification of new drugs to improve the current treatment or lower the risk of inducing resistance is urgently needed. Wasp venom primarily comprises peptides that are responsible for most of the biological activities in this poison. Here, a novel peptide Polydim-I, from Polybia dimorpha Neotropical wasp, was explored as an antimycobacterial agent. Polydim-I provoked cell wall disruption and exhibited non-cytotoxicity towards mammalian cells. Polydim-I treatment of macrophages infected with different M. abscessus subsp. massiliense strains reduced 40 to 50% of the bacterial load. Additionally, the Polydim-I treatment of highly susceptible mice intravenously infected with M. abscessus subsp. massiliense induced 0.8 to 1 log reduction of the bacterial load in the lungs, spleen, and liver. In conclusion, this is the first study to show the therapeutic potential of a peptide derived from wasp venom in treating mycobacteria infections. Polydim-I acts on the M. abscessus subsp. massiliense cell wall and reduce 40–90% of the bacterial load both in vitro and in vivo. The presented results encourage further studies on the use of Polydim-I as one of the components for M. abscessus subsp. massiliense treatment.